Anxiety in youth with asthma: A meta‐analysis. Issue 9 (27th July 2017) - Dudeney, Joanne; Sharpe, Louise; Jaffe, Adam; Jones, Emma B.; Hunt, Caroline
Abstract: OBJECTIVES: Anxiety often presents comorbidly with asthma in youth under 18; however, prevalence rates are unclear. The aim of this review was to provide an up‐to‐date analysis of the literature investigating the prevalence of anxiety disorders, and comparisons of anxiety disorders and symptomatology in youth with asthma, compared to those without. METHODS: A systematic search was conducted using the databases PsycINFO, MEDLINE, EMBASE, and CINAHL. RESULTS: The search process produced 15 studies ( n  = 7443) reporting data on youth with asthma and anxiety disorders, 11 studies ( n  = 10 332) reporting data on youth with and without asthma and anxiety disorders, and 28 studies ( n  = 5848) reporting data on youth with and without asthma and anxiety symptomatology. Youth with asthma had an anxiety disorder prevalence rate of 22.7%. Youth with asthma also had a greater number of anxiety disorders, compared to those without asthma ( d  = 0.37, 95%CI: 0.24‐0.50, P  < 0.001), and higher levels of anxiety symptomatology than youth without asthma ( d  = 0.29, 95%CI: 0.19‐0.39, P  < 0.001). CONCLUSIONS: Youth with asthma display a prevalence rate for anxiety disorders that is more than three times higher than the prevalence in healthy youth. For the specific anxiety disorders investigated, elevated prevalence rates for youth with asthma were also found. Future research needs to focus on the factors that mediate or predict the development and maintenance of anxiety in youth with asthma and the development of clinically efficacious treatments.